(untitled) (Research, Society and Development, 2021)
One of the main obstacles to the growth of the sheep herd are the losses caused by gastrointestinal helminthiasis. Thus, the present study aimed to evaluate the effect of two antiparasitic treatments for naturally infected sheep, using an allopathic treatment with Levamisol Hydrochloride 5% and a homeopathic treatment with the product Homeocapriovi Verm 100, comparing the differences in egg counts per gram of feces (OPG) and oocysts per gram of feces (OOPG) of treatments and serum concentrations of total proteins, globulins, albumin and the albumin/globulin ratio of allopathic and homeopathic treatments in the immune response to parasitic infections. After analyzing the results, both the allopathic product and the homeopathic product used in this study prevented the increase of OPG for infection by Strongylida helminths and both groups did not show clinical signs of coccidiosis. There was no significant difference between the two groups in the analysis of the mean serum concentration of total proteins, albumin, globulin and the albumin/globulin ratio. Although the cost has been higher in homeopathic treatment, it can be concluded that it is an efficient alternative in the control of parasites in the gastrointestinal tract of sheep.